Coinfections in hospitalized patients with severe fever with thrombocytopenia syndrome: A retrospective study. Issue 12 (3rd September 2022) - Ge, Hong‐Han; Wang, Gang; Guo, Pei‐Jun; Zhao, Jing; Zhang, Shuai; Xu, Yan‐Li; Liu, Yuan‐Ni; Ye, Xiao‐Lei; Wu, Yong‐Xiang; Li, Shuang; Yue, Ming; Ji, Wen‐Juan; et al.
Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick‐borne disease with a high case fatality rate. Few studies have been performed on bacterial or fungal coinfections or the effect of antibiotic therapy. A retrospective, observational study was performed to assess the prevalence of bacterial and fungal coinfections in patients hospitalized for SFTSV infection. The most commonly involved microorganisms and the effect of antimicrobial therapy were determined by the site and source of infection. A total of 1201 patients hospitalized with SFTSV infection were included; 359 (29.9%) had microbiologically confirmed infections, comprised of 292 with community‐acquired infections (CAIs) and 67 with healthcare‐associated infections (HAIs). Death was independently associated with HAIs, with a more significant effect than that observed for CAIs. For bacterial infections, only those acquired in hospitals were associated with fatal outcomes, while fungal infection, whether acquired in hospital or community, was related to an increased risk of fatal outcomes. The infections in the respiratory tract and bloodstream were associated with a higher risk of death than that in the urinary tract. Both antibiotic and antifungal treatments were associated with improved survival for CAIs, while for HAIs, only antibiotic therapy was related to improved survival, and no effect from antifungal therapy was observed. Early administration of glucocorticoids was associated with an increased risk of HAIs. The study provided novel clinical and epidemiological data and revealed risk factors, such as bacterial coinfections, fungal coinfections, infection sources, and treatment strategies associated with SFTS deaths/survival. This report might be helpful in curing SFTS and reducing fatal SFTS.